SOLUSI TEKNOLOGI INFORMASI DAN MANAJEMEN PRODUK SEBAGAI UPAYA UNTUK MENINGKATKAN PERAN USAHA MIKRO KECIL DAN MENENGAHDI DESA SENDANG TIRTO BERBAH SLEMAN - Sholeh, Muhammad; Hamzah, Amir; Susetyo, Joko (Universitas Muhammadiyah Semarang, 2015)
The development of technology especially Information and Communication Technology (ICT)provides new opportunities to overcome some of the problems of SMEs. Although not a majorproblem, but the opportunities brought by ICT is very large, and based on conditions on theground, indicate that the adoption of ICT by SMEs sector is still not up compared with largecompanies. Utilization of ICT can also be used for the promotion of SMEs. Likewise, in the processof cashew production and the processes of packaging still using simple tools so that productivitycan not be optimized. In the implementation of this IbM, the activities are divided into three. First:Activities are oriented towards activities stripping and processed cashew nuts. In stripping cashewergonomic equipment required in order to process cashew stripping can be done easily andactivities associated with the use of technology to processed of packaging. Second: the activitiesrelated to the promotion process Sendang Tirto by optimizing information technology. Theseactivities include building a village website Sendang Tirto, training for administrators so that thefilling process and the renewal of the website can be continuously carried out. Keywords: IbM, SMEs, Cashew, Sendang Tirto, ICT